Return on Equity as the Leading Indicator of Dividend Payout Ratio of Jakarta Islamic Index Stocks Listed on the Indonesia Stock Exchange - Budianto, Endi Trimawan; Eka Bertuah, Eka Bertuah (Dinasti International Journal of Management Science, 2020)
Dividend policy is a critical and imperative decision because it involves the shareholders interest’s and has a significant impact to company's sustainability. Sartono (2010) states that dividend policy is a decision whether the profits obtained by the company will be distributed to shareholders as dividend or will be held in the form of retained earnings for future investment.Brigham and Gapenski (2006) state that investor’s main purpose when investing their fund is to gain income or return either as dividend yield or as capital gain. On the other side, the company who will share the dividend will be faced with various consideration: the urge to retain some profit for a more promising re-investment, the company funding, company liquidity, shareholder’s characteristic, specific target related to dividend payment ratio, and other factors related to dividend policy.Based on the definition mentioned above, it can be concluded that dividend policy is influenced by two conflicting interests; the shareholders interest with their dividend and the company interest to do re-investment by retaining the profit. Therefore, dividends paid will depend on each company’s considerations.In general, the shareholders wish to have a relatively stable dividend share to minimize the uncertainty of expected investment result and to increase the shareholder’s trust toward the company so that the stock value will rise. The company dividend policy can be reflected by the Dividend Payout Ratio (DPR), which is the profit percentage shared in the form of cash dividend. It means that the size of the DPR, either big or small, will affect the shareholder’s decision and to the contrary it will also affect the company financial condition. Improper decisions will potentially envisage company facing funding difficulties in the future.According to Brigham and Gapenski (2006), the optimum dividend policy is the dividend policy which creating balance between the current dividend and its growth in the future so the company stock price can be maximized.Lintner (1956) argue that the company ability to gain profit is the main indicator of the company ability to pay dividend. So, the profitability is the most determining factor toward dividend. But some other research mention that the companies tend to choose new investment instead of paying high dividend if their condition are great, well-developed and have high profitability.The rapid growth of Islamic Finance become the first-rate consideration of choosing Jakarta Islamic Index stocks as the object research in which this research aimed to improve investor’s understanding related to dividend policy of sharia stocks member of Jakarta Islamic Index.